Handbook of natural gas transmission and processing : principles and practices - Mokhatab, Saeid; Poe, William A.; Mak, John Y. (Amsterdam : Gulf Professional Publishing is an imprint of Elsevier, 2015)
Written by an internationally-recognized author team of natural gas industry experts, the third edition of Handbook of Natural Gas Transmission and Processing is a unique, well-documented, and comprehensive work on the major aspects of natural gas transmission and processing. Two new chapters have been added to the new edition: a chapter on nitrogen rejection to address today's high nitrogen gases and a chapter on gas processing plant operations to assist plant operators with optimizing their plant operations. In addition, overall updates to Handbook of Natural Gas Transmission and Processing provide a fresh look at new technologies and opportunities for solving current gas processing problems on plant design and operation and on greenhouse gases emissions. It also does an excellent job of highlighting the key considerations that must be taken into account for any natural gas project in development.
Includes bibliographical references and index.
Keywords: Natural gas; Natural gas pipelines; Gas manufacture and works